An empirical assessment of relational competitive advantage in professional ship management - Gray, Richard; Panayides, Photis (My University, 1999)
Intense competition in many sectors across the maritime industry and in professional ship management in particular, means that the quest for achieving competitiveness will continue and intensify. A review of the current strategies across many sectors of the industry indicates the importance of forging stable partnerships for the achievement of competitiveness. Considering that the capability to form a relationship is an intangible resource (as depicted in resource-advantage theory), an empirical assessment in the context of ship management was undertaken. The assessment aimed to identify the type of relationships present in ship management, and succeeded in classifying those relationships into four distinct groups. The central thesis of the paper is that maritime organizations in general, and ship management companies in particular, may utilize their intangible relational resources in order to achieve competitive advantage. Based on the classification of ship management relationships, implications for managers are discussed
Keywords: Shipping--Management; Competitiveness (Economics); Transportation